Growing conifers from the seed - Greene, Rennie (My University, 1906)
Introduction: In the cultivation of any plant life, the question of the cheapest method of obtaining those plants presents itself. This is especially true of the man who would raise trees. And it doubly emphasizes itself upon the man who would raise his own evergreens. These trees are extremely hard to raise in a wind swept country like our own, and there are many questions to be solved to find the cheapest and best method, or methods, for propagating them in Kansas and especially in the western portion of the State. The first question which presents itself to the man who wishes an evergreen for an ornamental, is whether he shall obtain his trees from a nursery or raise them from the seed. If there are sent from the nurseries packed as they should be they would cost many times what these nurseries quote them at. Nurserymen offered pines of the Austrian and Scotch species at 35 cents apiece this spring, at Hays City. These were sturdy little trees three or three and one-half feet high and if they had been properly shipped they might have survived, but none lived. About ninety trees, of these same varieties, grown from seedlings set in 1903 at the Hays Experiment Station, were transplanted this spring and about 95% are growing now in May. This indicates that the nursery trees are the dearest in the end. Another consideration, however, is the distance removed from the nursery and the change of climate. If nursery trees are to be used, they should be obtained from the nearest point. There are many reasons to believe that the tree, grown from Kansas seed, on Kansas soil and acclimated to the drouth and winds of Kansas, has by far the better chance to survive.
Citation: Greene, Rennie. Growing conifers from the seed. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Horticulture; Silvicuture; Conifers; Evergreen Trees; Kansas; Theses